Congenital Bleeding Disorders amid the COVID-19 pandemic: Open questions and recommendations - Naderi, Majid; Malek , Fatemeh; Miri Aliabad , Ghasem; Behnampoor , Mahammad; Karimi, Mehran; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
This article reviews the current knowledges of congenital bleeding disorders (CBD) amid the COVID-19 pandemic. It appears that CBD is not associated with higher risk of getting COVID-19 and so the prevalence of COVID-19 among them seems not higher compared to the general population. In absence of specific therapeutic recommendations, it is essential to make a correct assessment of the risk of haemorrhage/thrombosis. Based on expert opinion, strategies for outpatient management include adherence to prescribed regimens, telemedicine, and communication about COVID-19 in patients with CBD. More data should be also collected to better characterize the impact of COVID-19 on patients with CBD. The current findings encourage further studies to determine the prevalence of SARS-CoV2 infection in CBD patients to understand more fully the burden of this novel pathogen and to develop adequate preventive measures against this infection.